Rancang Bangun Sistem Pendeteksi Kecelakaan Dan Tracking Lokasi Mobil Berbasis Android - Satri Asman; Werman Kasoep; Nefy Puteri Novani (CHIPSET, 2021)
This system is designed to know a car accident has happened and also to track a car location,when the accident happened, the system will send accident’s location data to user/familyAndroid application. Thus, user/family knows the accident and they can call the authorities orambulance as soon as possible to help accident’s victim. This system uses some componentssuch as Arduino Uno as a microcontroller, accelerometer sensor MMA7361 as an accelerationdetector, SIM808 Module as a GSM/GPRS network provider and also as GPS sensor. Thissystem tracks the car’s location continuously then the location will be displayed on maps ofAndroid application in the form of a blue marker. Based on this research the accelerationvalues of x-axis and y-axis of the accelerometer which are included in the accident category,which is ≥9g, when an accident occurs the system will send an accident notification toAndroid application and displayed on maps of Android application in the form of a redmarker, to inticipate of no internet connection an SMS with Google maps’s link of accidentlocation is also sent to the user/family.